L’orientation au travail des générations : le cas de la génération X au Québec - Charles Fleury (Sociologies, 2011)
This paper examines the evolution of work orientation of members of the X generation in Quebec whose difficulties of employability and youth values sparked multiple questions in the 1980s and early 1990s. Based on survey data collected between 1981 and 2006, it specifically examines the evolution of the importance given to work and the meaning of work in this generation when compared with other generations. It shows that unlike numerous theses defended by some youth sociologists in the 1980s and 1990s, work orientation of the members of the X generation differs little from other generations. It concludes that the specific economic difficulties experienced by members of X generation have not changed their work orientation in a typical and sustainable way.